Security assessment in active distribution networks with change in weather patterns - Jayaweera, D.; Islam, Syed (2014)
© 2014 IEEE. Security of supply of an active distribution network is constrained with increased presence of intermittent distributed generation, component outages, network constraints, change in weather patterns, and resource availability. Long term predictions of weather patterns are challenging, however, potential vulnerability of networks into change in weather patterns can be modeled with uncertainties distributing along the time frame of study. This paper investigates this problem in detail and proposes an improved approach to model the change in weather patterns and to assess the security of supply in an active distribution network. The approach incorporates Monte Carlo simulation and captures weather patterns in three modes dynamically. A case study is performed on a 24 bus active distribution network model, and the results suggest that the security of supply can be significantly affected with change in weather patterns. Change in weather patterns by 50% of the nominal weather can result in impacts on security of supply up to three times the nominal impacts.